Education, Health, and Economic Factors Affecting Secondary School Participation and Dropout Rates in Indonesia - Budi Suharto, Rahcmad; Hasanuddin, Hasanuddin; Jiuhardi, Jiuhardi; Lestari, Diana (The Es Economics and Entrepreneurship, 2025)
This study examines the influence of education, health, and economic factors on secondary school participation and dropout rates in Indonesia. Specifically, it investigates the effects of education expenditure, health expenditure, per capita GDP, student-teacher ratio, and student-class ratio on these educational outcomes, both directly and indirectly through graduation rates. Using panel data regression analysis, this study evaluates the relationships among these variables based on data from multiple provinces over a given period. The results reveal that education expenditure significantly increases graduation rates but does not directly enhance school participation. Health expenditure negatively affects graduation rates and does not significantly impact participation rates. Per capita GDP and the student-teacher ratio do not significantly influence participation rates but contribute to lower dropout rates. Meanwhile, the student-class ratio positively affects graduation rates but has no significant effect on school participation. These findings highlight the need for policy adjustments, including optimizing education funding, improving healthcare access for students, and strengthening economic support for families to reduce dropout rates. Additionally, balancing student-teacher and student-class ratios is essential for enhancing educational outcomes.